2005
DOI: 10.1111/j.1559-1816.2005.tb02143.x
|View full text |Cite
|
Sign up to set email alerts
|

Punitive Reactions to Completed Crimes Versus Accidentally Uncompleted Crimes

Abstract: Previous studies have shown that the harm caused by crime affects punitive reactions even if differences in the degree of harm are merely accidental. However, it remains unclear whether the effect is direct or whether it is mediated by attributed responsibility or blame. Participants were 303 university students who listened to 4 case vignettes (hetweensubjects design). Half received information about a completed crime and half about an accidentally uncompleted crime. Crime type was either Fraud or rape. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 34 publications
2
16
0
Order By: Relevance
“…With regard to how they manage children’s morally-relevant violations, then, parents show a marked sensitivity to the distinction between moral and conventional transgressions, whereas the distinction between intentional and accidental moral transgressions is much less pronounced. The present data from parents of 3–10-year-olds fit with recent studies showing that adults exhibit an ‘outcome bias’ in some situations when assessing how wrongdoers should be treated (e.g., Cushman, Dreber, Wang, & Costa, 2009; Oswald, Orth, Aeberhard, & Schneider, 2005). …”
Section: Discussionsupporting
confidence: 89%
“…With regard to how they manage children’s morally-relevant violations, then, parents show a marked sensitivity to the distinction between moral and conventional transgressions, whereas the distinction between intentional and accidental moral transgressions is much less pronounced. The present data from parents of 3–10-year-olds fit with recent studies showing that adults exhibit an ‘outcome bias’ in some situations when assessing how wrongdoers should be treated (e.g., Cushman, Dreber, Wang, & Costa, 2009; Oswald, Orth, Aeberhard, & Schneider, 2005). …”
Section: Discussionsupporting
confidence: 89%
“…Although the predictions are consistent with attribution theory, it is important to note that the demand for punishment has been found even when the harm was accidental (Greene & Darley, 1998). However, more recent evidence (Oswald, Orth, Aeberhard, & Schneider, 2006) has indicated that relationship between harm and punishment was not mediated by perceived blame. Therefore, in the present research the comparison between the intentional and accidental conditions for the triggerman will be a test of these conflicting views.…”
Section: The Present Studiesmentioning
confidence: 71%
“…One might postulate that, as Alicke (2000) suggested for outcome bias, the harm caused by an offense could provoke this same will to punish and thus produce similar experimental results. Certain results from a very recent work by Oswald, Orth, Aeberhard, and Schneider (2005) follow this hypothesis. In their research, in which they varied the degree of objective consequences (rape or attempted rape), they showed through responsibility-punishment assessment (normal order), that punishment was very weakly correlated with responsibility.…”
mentioning
confidence: 75%
“…The research of Oswald et al (2005) suggests that in case of severe outcomes, when responsibility is presented first (normal order), there is not necessarily a link between responsibility and punishment. This conforms with Fauconnet's (1920) analyses and the results obtained by Oberlé and Gosling (2004) for stigmatized targets, in normal order, when a justification model is activated (where punishment is initially independent and not function of responsibility).…”
mentioning
confidence: 99%